Acclimation and Characterization of Marine Cyanobacterial Strains Euryhalinema and Desertifilum for C-Phycocyanin Production - Khazi, Mahammed Ilyas; Li, Chenshuo; Liaqat, Fakhra; Malec, Przemyslaw; Li, Jian; Fu, Pengcheng (Frontiers in Bioengineering and Biotechnology, 2021)
This study involves evaluation of two native cyanobacterial strains Euryhalinema and Desertifilum isolated from a mangrove pond in Haikou (China) for their possible phycocyanin (C-PC) production. Maximal growth rate with highest chlorophyll and C-PC accumulation were observed at 28°C and 60 μmol photons m−2 s−1 photon flux density for Euryhalinema sp., while for Desertifilum sp. at 32°C and 80 μmol photons m−2 s−1. Nitrogen and iron concentration trails revealed that double strength concentration of sodium nitrate and ferric ammonium citrate in original BG11 media increased growth rate and accumulation of C-PC for both strains. Three different C-PC extraction methods were tested. The combined extraction protocol of freeze–thaw and ultrasonication markedly increased the C-PC extraction efficiency and attained the food grade purity (A620/A280 ratio >0.7), whereas a higher C-PC yield was found with Na-phosphate buffer. Furthermore, the clarified crude extract was used to purify C-PC by fractional ammonium sulfate [(NH₄)₂SO₄] precipitation, Sephadex G-25 gel filtration chromatography, and DEAE-sephadex ion exchange chromatography and attained analytical grade purity (A620/A280 ratio >3.9). Taken together, both strains showed their potential to be domesticated for valuable phycocyanin production.